Dominant-Negative Mutations in α-II Spectrin Cause West Syndrome with Severe Cerebral Hypomyelination, Spastic Quadriplegia, and Developmental Delay - Saitsu, Hirotomo; Tohyama, Jun; Kumada, Tatsuro; Egawa, Kiyoshi; Hamada, Keisuke; Okada, Ippei; Mizuguchi, Takeshi; Osaka, Hitoshi; Miyata, Rie; Furukawa, Tomonori; Haginoya, Kazuhiro; Hoshino, Hideki; et al. (American journal of human genetics, 2010)
A de novo 9q33.3-q34.11 microdeletion involving STXBP1 has been found in one of four individuals (group A) with early-onset West syndrome, severe hypomyelination, poor visual attention, and developmental delay. Although haploinsufficiency of STXBP1 was involved in early infantile epileptic encephalopathy in a previous different cohort study (group B), no mutations of STXBP1 were found in two of the remaining three subjects of group A (one was unavailable). We assumed that another gene within the deletion might contribute to the phenotype of group A. SPTAN1 encoding α-II spectrin, which is essential for proper myelination in zebrafish, turned out to be deleted. In two subjects, an in-frame 3 bp deletion and a 6 bp duplication in SPTAN1 were found at the initial nucleation site of the α/β spectrin heterodimer. SPTAN1 was further screened in six unrelated individuals with WS and hypomyelination, but no mutations were found. Recombinant mutant (mut) and wild-type (WT) α-II spectrin could assemble heterodimers with β-II spectrin, but α-II (mut)/β-II spectrin heterodimers were thermolabile compared with the α-II (WT)/β-II heterodimers. Transient expression in mouse cortical neurons revealed aggregation of α-II (mut)/β-II and α-II (mut)/β-III spectrin heterodimers, which was also observed in lymphoblastoid cells from two subjects with in-frame mutations. Clustering of ankyrinG and voltage-gated sodium channels at axon initial segment (AIS) was disturbed in relation to the aggregates, together with an elevated action potential threshold. These findings suggest that pathological aggregation of α/β spectrin heterodimers and abnormal AIS integrity resulting from SPTAN1 mutations were involved in pathogenesis of infantile epilepsy.